The value of a short practical training course for newly qualified therapists working with children with cerebral palsy in South Africa - Bakuwa, Takondwa (My University, 2018)
Background: Cerebral palsy (CP) is one of the most complex disabling disorders in children that newly qualified therapists face in practice. Newly qualified therapists do not feel prepared to deal with complex conditions despite being expected to. Short practical training courses could potentially help bridge this gap in readiness. The aim of the study was to determine the value of the practical training course on CP to the practice of newly qualified therapists. Methods: Secondary analysis of therapists’ course evaluation records from eleven short practical training courses was done. Mixed methods were used to establish expectations of course participants, change in their level of CP knowledge, aspects of the course deemed useful for CP practice and change in attitudes, perceptions and practice intents. Results: Course expectations of the majority of the therapists were met, most of whom reported having also gained skills and confidence. Significant change was observed in the self-perceived level of knowledge in various aspects of CP after the course (p < .001). Aspects on communication and play therapy showed the most significant difference (p < .001). Therapists appreciated adult teaching and learning methods, conducive learning environment, the relevant and organised content and holistic approach of the course. They reported readiness to adopt positive attitudes and perceptions and practice. Conclusion: A short practical training course was therefore valuable in addressing the perceived lack of readiness amongst newly qualified therapists working with children with CP. It was capable of improving their knowledge and changing their attitudes, perceptions and practice intentions positively.
A research report submitted to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy, November 2018
Keywords: Newly Qualified Therapist; Cerebral Palsy; Child; Preceptorship (Practical Training)